Intermediate economic statistics - Fox, Karl August (New York : Wiley, 1968)
This is intermediate text on economic statistics with focus on economics and statistics, economic concepts, simple regression and the measurement of economic relationships. Other areas covered include: multiple regression; time series; analysis of variance; structural analysis of economic time series; measurement of economic aggregates and others.
Includes bibliographical references and index.
lje 23/1/19
Loans
Keywords: Econometrics; Statistics; Economics